مغلیہ دورمیں وحدت ادیان کی اہم کاوشیں اور ان کے اثرات :ایک تحقیقی جائزہ: Major Efforts of unification of religions in the Mughal period and their Impacts :A Research Review - Dr Nadia Alam; alazhari, ali akbar (MEI, 2023)
Soon after the arrival of Islam in India, it began emerging as a strong power through the work of Muslim Scholars and Sufis. To minimize its strength, various efforts were made by several Hindu reformers to either assimilate it with other regional religions or unify it with other religions to promote the so-called concept of “peace & love for all”. These efforts gave rise to different religions and movements, most important of which are Sikhism and Bhakti Movement. Although they began with the benign objectives to weaken the power of Islam and assimilate it with other religions to prevent more conversions, with the passage of time the nature of these movements became clearly anti-Islamic and hostile. Similarly, the ideologies of Akbar and Dara Shikoh gave rise to Din-e-Ilahi and the un-Islamic concepts of unification of religions and peace & love for all. The article in hand presents an overview of the propagators of these anti-Islamic efforts, their popularity and impacts on the Muslim society in India during the Mughal period. The aim is to provide a historical context of such movements and the efforts made by Muslim scholars to combat these insurgencies in order to provide guidance to the Muslims in the present era where print, electronic and social media have made false and misleading information very easily accessible to all. It can be witnessed even now that on these media the propagators of such concepts are derailing the people by saying that goodness and piety do not belong to any particular religion. Allah and Ram are the names of one personality and goal of life is the same irrespective of any religion.